A influência do processo Educacional na qualidade de vida dos idosos a luz da teoria do autocuidado de orem. - (:unkn) unknown (Universidade Federal do Amazonas - Universidade do Estado do Pará, 2014)
With the change of the demographic profile of the population the aging became a theme discussed daily, several are the actions ruled in the National politics of the senior and active aging with the intention of improving the quality of life of the aging, among these actions is the senior's education, that has as main objective, to promote the health and as consequence the self-care. The open university of the third age appears as the favorable place to discuss the seniors' demands, as well as to insert them in the education method, approaching pertinent themes and promoting the life quality. This work has as objective to analyze the influence of the educational process in the quality of the seniors' life under the light of the theory of the self-care of Orem. It is about a transversal study, descriptive with quantitative/qualitative approach that resorting of the triangulation method of data; The participants of the study were 131 senior visitors of the workshops of the Open University related to the health of the Third Age (UnaTI), that answered two instruments of data collection, a questionnaire on the profile sociodemographic, socioeconomic, socioeducational and sociocultural of the seniors, the questionnaire of quality of life of Whoqol, of these, 11 seniors still answered an interview itinerary. The data demonstrated that the seniors participants of the workshops of health of UnaTI, are in majority women, (86,3%), with medium age of 66,7 years old, without spouse (65,9%), having from 01 to 03 children, living in their own homes, multigenerational, winning from 01 to 03 minimum salary. About the life quality the results found indicate the self-perception of life quality as "good" with a representation of (69,4%), in the environmental domain (67,7%), in the psychological domain (67,7%) and in the domain of social relationships (67,1%), indicating a good quality of the seniors' life. The searching for friendships, occupation of the free time, escape from the solitude, looks for education in health, the searching for vitality and ease of family problems and of health had been constituted in reasons that take the senior to enter in UnaTI. About the senior's existences, inside of the educational process the results found were: comfort, good sensation for feeling supported, good sensation for feeling respected in their limits, perception of rights broken, learning difficulty and unsafe sensation. About the modifications accomplished through the influence of the educational process, were identified the feeling of overcoming of fears and family problems, the elevation of the self-realization, and the self esteem sensation. In the face of the subjects discussed in the study, it is notorious the improvement of the life quality, the changes of habits and the accomplishment of the sel-care, motivated during the educational process, that provides to the senior the knowledge so that they identify their needs and practices, according to Dorothéa Orem theory, that works the promotion of the self-care through the diffusion of educational practices that provide the improvement of the life quality. In that scenery the nurse is the more qualified professional to act as coordinator identifying the senior's specificities for later work the most appropriate method, that promotes in a correct way the self-care, being able to be based in theoretical like Orem, because his premise is that the senior population should be oriented that the main responsible for their health are themselves.
Keywords: Educação.; Idoso; Qualidade de vida; Autocuidado; Enfermagem; Education; Senior; Life Quality; Self-care; Nursing; CIÊNCIAS DA SAÚDE: ENFERMAGEM